Letter (copy) : Patent Leather Shoes for Basque Children - Tewson, Vincent
1938-10-18 038-0116-004 Secretary's. HVT/FC/EK/138. 18th October, 1938. Mr. W. Newman, The Co-operative Wholesale Society, Leman Street, London, E.C. Dear Mr. Newman, PATENT LEATHER SHOES FOR BASQUE CHILDREN. Some time ago I made an enquiry from the Manager of the Boot Department in regard to first quality patent leather ankle strap shoes for girls. I think the price of these is about 6/6 a pair. One of the difficulties was ascertaining the girls' sizes and it was finally decided that we would get cut-outs of the shape of the girls' feet. I am enclosing these shapes and shall be glad if the shoes can be sent as soon as possible to: The Basque Children's Home, Rowley Lodge, Arkley, Near Barnet, Herts. and the account sent to me personally at this office. Yours sincerely, Shapes. 292/946/38/118(I)